2021
DOI: 10.1063/5.0045324
|View full text |Cite
|
Sign up to set email alerts
|

Dominant recombination path in low-bandgap kesterite CZTSe(S) solar cells from red light induced metastability

Abstract: Hetero-junction kesterite Cu 2 ZnSn(S,Se) 4 solar cells with low bandgap obtained from three different methods of fabrication were exposed to red light illumination, and the changes observed in their electronic properties due to this exposure were studied via open circuit voltage transients, admittance spectroscopy, capacitance voltage profiling techniques, and SCAPS simulation fits to experimental data. The results from the aforementioned techniques, in combination with temperature-dependent current voltage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This hypothesis could also explain why the two cell types with 20-nm and 30-nm buffers without PDT are affected much less by the photoexcitation of the buffer: Monitoring the V OC under red illumination over time reveals a decrease of the V OC transients in these two cell types (these measurements were done by colleagues at the Martin Luther University Halle-Wittenberg). This indicates that these cells are limited by interface recombination [25,26] (also seen in the V OC , cf. Tab.…”
Section: Buffer Excitationmentioning
confidence: 91%
“…This hypothesis could also explain why the two cell types with 20-nm and 30-nm buffers without PDT are affected much less by the photoexcitation of the buffer: Monitoring the V OC under red illumination over time reveals a decrease of the V OC transients in these two cell types (these measurements were done by colleagues at the Martin Luther University Halle-Wittenberg). This indicates that these cells are limited by interface recombination [25,26] (also seen in the V OC , cf. Tab.…”
Section: Buffer Excitationmentioning
confidence: 91%
“…It has been identified that for the Se-rich composition the main recombination pathways lie in the space-charge region (SCR), that is, in the bulk of the absorber. [14][15][16][17][18][19][20][21][22] Since the potential of kesterite materials as photovoltaic absorbers was identified, most of the publications have aimed to suppress the numerous detrimental effects of the proliferating secondary phases, while optimizing carrier concentration by controlling the Cu, Zn, Sn, and S/Se chemical potentials, that is, optimizing intrinsic doping. [23][24][25][26] This leads to constraints on the growth conditions to a compositional region where the impact of secondary phases is minimum.…”
Section: Introductionmentioning
confidence: 99%
“…It has been identified that for the Se‐rich composition the main recombination pathways lie in the space‐charge region (SCR), that is, in the bulk of the absorber. [ 14–22 ]…”
Section: Introductionmentioning
confidence: 99%